MENANAMKAN SIKAP KEJUJURAN PADA SISWA - Abdullah Isa (Tarunaedu: Journal of Education and Learning, 2023)
This article discusses the efforts of Islamic Religious Education Teachers to Instill the Value of Honesty in Grade 7 Students of Bina Taruna Middle School Surabaya for the 2022-2023 Academic Year. This article is the result of qualitative research using primary and secondary data sources. Meanwhile, data collection was carried out using observation, interviews and documentation methods. The aim of this research is to find out how Islamic Religious Education Teachers Efforts to Instill the Value of Honesty in Class 7 Students of Bina Taruna Surabaya Middle School for the 2022-2023 Academic Year, to observe and see the efforts of Islamic Religious Education Teachers in instilling the value of honesty in the learning process and its obstacles. Islamic Religious Education Teachers' Efforts to Instill the Value of Honesty in Grade 7 Students of Bina Taruna Surabaya Middle School for the 2022-2023 Academic Year, with the value of honesty in students really helping teachers in delivering material and assignments, therefore students can easily understand instilling the value of honesty. The results of this research can be said to be effective because students are honest and enthusiastic during the learning process so that the assignment collection process is not hampered.